1994
DOI: 10.1002/gcc.2870090303
|View full text |Cite
|
Sign up to set email alerts
|

Polysomy of chromosome 12 in 60 patients with non‐hodgkin's lymphoma assessed by fluorescence in situ hybridization: Differences between follicular and diffuse large cell lymphoma

Abstract: Sixty consecutive evaluable specimens from patients with non-Hodgkin's lymphoma (NHL) were studied for the incidence of polysomy of chromosome 12 by fluorescence in situ hybridization (FISH) with probes for the repetitive DNA sequence in the centromeric region of chromosome 12. Thirty-six samples were from follicular lymphomas (FLs), and twenty-four were from diffuse large cell lymphomas (DLCLs). Fifty-two specimens (86%) were obtained by fine-needle aspiration of a diseased node, seven (11.6%) were from invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…Two commonly gained subregions were mapped to 12q13-q14 and 12q24. In line with our results, polysomy of chromosome 12 was detected as the most common abnormality in B-cell malignancies studied by fluorescence in situ hybridization (59). In addition, previous CGH studies reported gains and/or amplifications on 12q as recurrent aberrations in various types of non-Hodgkin lymphomas, including extracerebral DLBCL (3,5,6,22,35,55).…”
Section: Discussionsupporting
confidence: 90%
“…Two commonly gained subregions were mapped to 12q13-q14 and 12q24. In line with our results, polysomy of chromosome 12 was detected as the most common abnormality in B-cell malignancies studied by fluorescence in situ hybridization (59). In addition, previous CGH studies reported gains and/or amplifications on 12q as recurrent aberrations in various types of non-Hodgkin lymphomas, including extracerebral DLBCL (3,5,6,22,35,55).…”
Section: Discussionsupporting
confidence: 90%
“…The diVerence was even more signiWcant when comparing FL grades 1-3a versus FL grade 3b and DLBCL (Table 3). Trisomy 12 has been reported more frequently in primary diVuse large cell lymphoma than in secondary DLBCL following FL (Younes et al 1994). Our data showed the same tendency but the diVerence was not signiWcant.…”
Section: Discussionsupporting
confidence: 77%
“…However, the relative incidence of trisomy 12 in diffuse large B cell lymphoma does not appear to be greater than the incidence among cases of non-Hodgkin lymphoma in general. 20,25,43,67,80,82,86,87,90 Trisomy 7 occurs with approximately the same frequency as trisomy 12 in non-Hodgkin lymphoma. Trisomy 7 has been identified most frequently in association with t(14;18) and in transformed diffuse large B cell lymphoma, suggesting that this abnormality in both PELs and KSHV-positive solid lymphomas is unusual.…”
Section: Discussionmentioning
confidence: 95%